(untitled) (Filologia e Linguística Portuguesa, 2020)
The present work focuses on presenting the elaboration process of a diplomatic edition of satirical songs – or cantigas satíricas – of the Cancioneiro da Biblioteca Nacional (Colocci-Brancuti) – also known as the Biblioteca Nacional’s Songbook – with the purpose of developing a finite and infinitive verbal forms vocabulary, patented in these songs, being produced based upon the Historical Lexicography precepts, with the intention of contributing to the work of reconstructing the trajectory of the Portuguese language during the archaic period. Emphasized here is the importance of the access to the remaining documents through digital archives provided by some libraries and their platforms, which has allowed the observance of the linguistic data richness of these codices in order to preserve all aspects that could offer clues to an investigation and registration of the patented language in troubadour songs.